2012
DOI: 10.1111/j.1530-0277.2011.01699.x
|View full text |Cite
|
Sign up to set email alerts
|

Heritability of Level of Response and Association with Recent Drinking History in Nonalcohol‐Dependent Drinkers

Abstract: Background Level of response to alcohol (LR) has been shown to be associated with the risk for developing alcohol dependence and can be measured using the Self-Rating of the Effects of Alcohol (SRE) questionnaire. This study examined the heritability of the SRE-measured level of response and the relationship between LR and recent alcohol drinking history (RDH) in a predominantly African American non-alcohol dependent population. Methods This was a sibling study of 101 social drinkers aged 21–35 years recruit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 40 publications
0
30
0
Order By: Relevance
“…As summarized in a recent meta-analysis, populations at risk for AUD, such as individuals with a family history of alcoholism, typically have lower LR compared to other populations [45]. Heritability ( h 2 ) estimates for LR are approximately 60% [46, 47]. …”
Section: Evaluating the Weight Of Evidence For Aud Candidate Endophenmentioning
confidence: 99%
“…As summarized in a recent meta-analysis, populations at risk for AUD, such as individuals with a family history of alcoholism, typically have lower LR compared to other populations [45]. Heritability ( h 2 ) estimates for LR are approximately 60% [46, 47]. …”
Section: Evaluating the Weight Of Evidence For Aud Candidate Endophenmentioning
confidence: 99%
“…A study in young adult Australian twins showed that a composite alcohol sensitivity measure, combining subjective intoxication and increase in body-sway after alcohol challenge had a heritability of 0.60 (Heath et al, 1999). A sibling study in young adult social drinkers concluded that the heritability of the SRE was 0.67 (Kalu et al, 2012). Since the longitudinal studies described above have shown that a low LR to alcohol predicts the development of alcoholism, a low LR can be considered as an intermediate phenotype to search for candidate genes for alcoholism (Enoch et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…People with a low LR are more likely to become alcoholic than people with a high LR (5,6), and the LR phenotype is heavily genetically influenced (7). Therefore, determining the factors that contribute to LR is a promising approach for the identification of abuse liability loci.…”
mentioning
confidence: 99%